Development of the Thermoacoustic Refrigerator System Using a Stack made of some Stainless Steel Mesh and a Hot Heat Exchanger - Haris S Dyatmika; Wahyu Nur Achmadin; Prastowo Murti; I. Setiawan; Agung B S Utomo (Institut Teknologi Bandung, 2015)
In order to develop and increase the performance of a thermoacoustic refrigerator system, a research has been conducted. In this research a PVC cylindrical pipe (diameter of 5.5 cm and length of 80 cm) as a tube resonator, a loudspeaker as a sound source, some stainless steel mesh as a stack and a hot heat exchanger were arranged to be a thermoacoustic refrigerator system. The results show the influence of cooling power by utilizing some stainless steel mesh stack, the power of the utilized sound, and a hot heat exchanger on the performance of the thermoacoustic system. We expected to construct a thermoacoustic refrigerator system, which has an optimally performance, by using some stainless stell mesh as stack and a hot heat exchanger.